Origin and Evolution of Deep Brain Stimulation - Sironi, Vittorio Alessandro (Frontiers in Integrative Neuroscience, 2011)
This paper briefly describes how the electrical stimulation, used since antiquity to modulate the nervous system, has been a fundamental tool of neurophysiologic investigation in the second half of the 18th century and was subsequently used by the early 20th century, even for therapeutic purposes. In mid-20th century the advent of stereotactic procedures has allowed the drift from lesional to stimulating technique of deep nuclei of the brain for therapeutic purposes. In this way, DBS was born, that, over the last two decades, has led to positive results for the treatment of medically refractory Parkinson's disease, essential tremor and dystonia. In recent years, the indications for therapeutic use of DBS have been extended to epilepsy, Tourette's syndrome, psychiatric diseases (depression, obsessive-compulsive disorder), some kinds of headache, eating disorders and the minimally conscious state. The potentials of the DBS for therapeutic use are fascinating, but there are still many unresolved technical and ethical problems, concerning the identification of the targets for each disease, the selection of the patients and the evaluation of the results.